1978
DOI: 10.2307/3428876
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Radionuclides by Plants as a Monitor System

Abstract: The accumulation of radionuclides by plants acting as a monitoring system in the environment may occur by two modes; foliar absorption by the leaves and shoot ofthe plant, or by root uptake from the soil. Data on plant accumulation of radionuclides may be obtained from studies of fission product radionuclides deposited as worldwide fallout, and from tracer studies of plant physiology.The epidermal features of plant foliage may exert an effect upon particle retention by leaves, and subsequent uptake of radionuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…However, Sr, like Ca, seems unable to move along the phloem [38,151,152] or this ability is strongly reduced. These tissues participate in the long-distance transport of metal ions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Sr, like Ca, seems unable to move along the phloem [38,151,152] or this ability is strongly reduced. These tissues participate in the long-distance transport of metal ions.…”
Section: Resultsmentioning
confidence: 99%
“…Both Sr and Ni were observed in the phloem elements (Figs. However, Sr and Ca are seemingly unable of phloem translocation [38,151,152] or this capacity is strongly reduced. The feasibility of Ni transport along the phloem was shown previously [150].…”
Section: Conducting Tissuesmentioning
confidence: 99%
“…Radionuclides could reach foliar surfaces by means of fugitive dust emissions from remedial action activities with subsequent deposition of contaminated particulate matter on adjacent vegetation. Radionuclides adsorbed on the surface of particles retained on plant foliar surfaces are likely to be available for foliar uptake and subsequent accumulation (Koranda and Robison 1978). However, techniques intended to minimize fugitive dust emissions (e.g., water sprays) are likely to be employed during remedial action activities.…”
Section: Factors Influencing Radionuclide Uptake By Plantsmentioning
confidence: 99%
“…On the basis of research with various trace metals, it can be concluded that the solubilization of radionuclides is determined largely by the form and concentration of the radionuclides involved as well as by the physicochemical characteristics of soil. Important soil characteristics include: soil solution composition; conductivity; pH; quantities of various clays and humic, fulvic, and other organic complexes present; type and density of charge on soil colloids; soil organic matter concentration and composition; and amount of reactive surface area (Cataldo and Wildung 1978;Koranda and Robison 1978). These phenomena are in turn dependent upon other properties of soil such as: particle size distribution; quantity and reactivity of hydrous oxides, carbonates, phosphates, sulfates, and other anions; mineralogy; degree of aeration; and microbial activity.…”
Section: Factors Influencing Radionuclide Uptake By Plantsmentioning
confidence: 99%
“…[6] Water hyacinths can also remove and retain heavy metals from aquatic systems. [11] In most cases, the removal of toxic metals does not have a fatal impact on the plants, and the metals are incorporated and sequestered from the immediate environment. [9,10] Even radionuclides can be taken up and accumulated by plants.…”
Section: Introductionmentioning
confidence: 99%